IDENTIFIKASI SPESIES CANDIDA PENTING MENGGUNAKAN METODE PCR DAN CHROMagar - , Suyana; , dr. Tri Wibawa, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Candidiasis is an infection of acute or subacute caused by Candida albicans Candida species or the other, which can attack various body tissues. Candida species are considered to be the biggest cause of infectious disease in humans. Based on where the infection, candidiasis divided into three types, namely: mucous membrane candidiasis, kutis candidiasis and systemic candidiasis. There are about 154 species of fungus Candida shows the level of resistance to antifungal different. Determining the species level is really important to do, because of the similarity between the phenotypes of Candida species is very high. Early diagnosis of fungal infection is important to reduce the level of patient deaths due to antifungal drug resistance. Candidiasis in laboratory examination is generally limited to the genus of fungi that infect, while the examination to the species level has not been much done. This study aimed to identify the fungus Candida sp using comparison of two methods: Polymerase Chain Reaction (PCR) and culture CHROMagar with primer pair. The research sample is a collection of 78 isolates of Candida results in Section of Microbiology, Faculty of Medicine UGM. First isolates of Candida savings DNA extraction, PCR amplified and electrophoresed Candida species were identified based on differences in the DNA fragments through the observation of the UV transilluminator. Later the same Candida isolates were cultured on CHROMagar medium angled tube, and Candida species were identified based on colony color differences are formed. The identification results obtained with the PCR method, species frequency Candida albicans 75.64%